The peasant questions from Marx to Lenin: the Russian experience - Chandra, Nirmal Kumar (2002)
What is a class? Do peasants constitute a single class? What is the peasant question from the Marxists' revolutionary perspective? These issues are raised in this paper, based on the writings of Marx, Engels and Lenin, above all. The empirical part, mainly on the Russian agrarian scene from the 1890s to 1930, explores if the peasants constituted a cohesive social force free from internal contradictions. There is also a brief discussion on the post-Soviet situation. - Reproduced.
Keywords: Peasantry